Tradisi Hukum Adat Pati Nyawa Lintas Etnis Melayu Islam dan Dayak Kabupaten Kapuas Hulu - Bibi Suprianto (IAIN Ponorogo, 2021)
AbstractThis Malay customary law contains a set of rules or behavioral norms that have consequences if violated. This illustrates that customary law has big consequences if it is violated and opposed by the community. The implementation of the law is generally reflected in the dispute over the disputed land which ends with a fine, as happened in the customary law of Pati Nyawa Cross Ethnic Malay Islam and Dayak. This paper discusses the customary law tradition of Pati Nyawa Cross Ethnic Kapuas Hulu Regency. This paper aims to determine the purpose of the establishment of the Pati Nyawa customary law across ethnic Malay Islam and Dayak Kapuas Hulu Regency. This research uses descriptive-analytical method. The results of the analysis show that in customary law this symbolizes the symbol of maintaining village peace and community comfort as well as the laws described in various villages through customary law documents. The customary law covering the sub-district is about the customary law of politeness that must be obeyed by local people and immigrants who want to visit the place as well as a chapter on marriage which explains how the marriage process is, the conditions specified in marriage to be able to comply with village customs and regulations local. AbstrakHukum adat Melayu ini memuat seperangkat aturan atau norma berprilaku yang punya konsekuensi apabila dilanggar. Hal ini menggambarkan bahwasanya hukum adat mempunyai konsekuensi yang besar jika dilanggar dan ditentang oleh masyarakat. Pelaksanaan hukum tersebut secara umum tercermin dalam perebutan tanah sengketa yang diakhiri dengan denda sebagaimana yang terjadi pada hukum adat Pati Nyawa Lintas Etnis Melayu Islam dan Dayak. Makalah ini membahas tradisi hukum adat Pati Nyawa Lintas Etnis Kabupaten Kapuas Hulu. Tulisan ini bertujuan mengetahui maksud dibentuknya hukum adat Pati Nyawa Lintas Etnis Melayu Islam dan Dayak Kabupaten Kapuas Hulu. Penelitian ini menggunakan metode deskriptif-analitis. Hasil analisis menunjukkan dalam hukum adat ini melambangkan simbol menjaga ketentraman desa dan kenyamanan bermasyarakat dan juga hukum-hukum yang dijelaskan dalam berbagai desa melalui dokumen-dokumen hukum adat. Hukum adat yang meliputi Kecamatan tersebut tentang hukum adat kesopanan yang harus dipatuhi oleh orang setempat dan orang pendatang yang ingin berkunjung ke tempat tersebut serta bab tentang perkawinan yang menjelaskan tentang bagaimana proses perkawinan, syarat-syarat yang ditentukan dalam perkawinan untuk dapat mematuhi adat dan peraturan desa setempat.